Graphic Design Visionaries - Roberts, Caroline, 1966- (Visionaries., 2015)
* Examines 75 visionary designers, telling the story of graphic design over the last 100 years.* Packed with stunning examples from all the greats of graphic design* An inspirational book for anyone interested in graphic design.